Effect of Supplementation of Lambs with Whole Cottonseed: Impact on Serum Biomarkers and Infection by Gastrointestinal Parasites under Field Conditions - Kozlowski Neto, Vitoldo Antonio [UNESP]; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Rubio, Camila Peres; Silva, Naiara Mirelly Marinho da [UNESP]; Tardivo, Renata [UNESP]; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Cerón, José Joaquín; Tvarijonaviciute, Asta; Amarante, Alessandro Francisco Talamini do [UNESP] (MDPI, 2023)
The purpose of this trial was to evaluate serum levels of oxidative stress biomarkers and biochemical analytes in crossbred lambs during the rearing phase in an integrated crop-livestock system (ICLS) to control gastrointestinal parasites. The experiment used 36 crossbred lambs (cross: Ile de France × White Dorper × Texel) divided into two groups. The WCS group was supplemented with whole cottonseed (WCS), and controls had no supplementation. Body weight, blood collection, and fecal analysis of nematode eggs and Eimeria oocysts counting per gram of feces were performed for each animal within 84 days of experiment. The following serum analytes were determined: total protein, albumin, globulin, cholesterol, haptoglobin, and 10 oxidative stress biomarkers: cupric reducing antioxidant capacity, ferric reducing ability of plasma, trolox equivalent antioxidant capacity, thiol, uric acid, paraoxonase-1, total oxidant status, ferric-xylenol orange, advanced oxidation protein products, and reactive oxygen metabolites derived compounds. The inclusion of WCS suggested the benefit in controlling infection as well as inducing an increase in antioxidants and a decrease in oxidants in lambs naturally infected by gastrointestinal parasites. The combination of WCS and ICLS could be a useful tool in controlling gastrointestinal parasite infection without affecting the production performance.
Keywords: antioxidant; biochemical analytes; Eimeriaspp; gastrointestinal nematodes; integrated crop-livestock system; oxidant; sheep